2008
DOI: 10.1177/0093854808328653
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Impulsive Beholder

Abstract: Substantial evidence indicates that impulsivity is a robust correlate of offending. However, its effects appear to be partially contingent upon other criminological factors, such as neighborhood context. The research examining the moderating influence of neighborhoods on the impulsivity-offending relationship has yielded inconsistent findings. The current analysis further investigates the possible interaction by exploring different types of impulsivity-related traits, perceptions of neighborhood informal socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Impulsivity in general has been found to relate to dysfunctional and distorted cognitions and workplace deviance (Henle, 2005;Mobini, Pearce, Grant, Mills, & Yeomans, 2006), and in particular, lower premeditation is associ ated with a variety of dysfunctional behaviors such as criminal behavior and alcohol-related problems (Jones & Lynam, 2009;King, Karyadi, Luk, & Patock-Peckham, 2011;Lynam & Miller, 2004). Individuals who are lower in premeditation do not strongly consider the consequences of their actions and may be unable or unwilling to weigh the advantages and disadvantages of a partic ular behavior before acting on it (Whiteside & Lynam, 2001).…”
Section: Premeditationmentioning
confidence: 99%
“…Impulsivity in general has been found to relate to dysfunctional and distorted cognitions and workplace deviance (Henle, 2005;Mobini, Pearce, Grant, Mills, & Yeomans, 2006), and in particular, lower premeditation is associ ated with a variety of dysfunctional behaviors such as criminal behavior and alcohol-related problems (Jones & Lynam, 2009;King, Karyadi, Luk, & Patock-Peckham, 2011;Lynam & Miller, 2004). Individuals who are lower in premeditation do not strongly consider the consequences of their actions and may be unable or unwilling to weigh the advantages and disadvantages of a partic ular behavior before acting on it (Whiteside & Lynam, 2001).…”
Section: Premeditationmentioning
confidence: 99%
“…Moreover, research shows that as a key individual characteristic, self-control exists on a continuum within individuals (Tangney et al 2004). Lower self-control relates to greater impulsivity (Jones and Lynam 2009;Nagin and Pogarsky 2001), criminality, and deviance (Gottfredson and Hirschi 1990), and higher self-control relates to increased behavioral deliberation . For example, compared with their counterparts with higher self-control, individuals with lower self-control often react quickly because they give less consideration to their behaviors before acting to derive near-term benefits at the expense of longerterm payoffs .…”
Section: Self-control As a Primary Intrinsic Control That Inhibits In...mentioning
confidence: 99%
“…Rook (1987) postulated that different people show various tendencies for impulse buying. According to Jones and Lynam (2009), there are a variety of scales to evaluate the tendency of consumers' impulse buying. From the previous studies, it is therefore concluded that reasons for impulse buying are different in different people and it may also be affected by the lifestyle of individuals.…”
Section: Literature Reviewmentioning
confidence: 99%